(untitled) (Padmakanya Journal of Science and Technology, 2025)
Solid waste management (SWM) remains a critical environmental challenge in rapidly urbanizing cities of developing countries, including Nepal. This study aimed to assess the knowledge, attitudes, and practices (KAP) toward SWM among households (HHs) in Wards 5 and 7 of Biratnagar Metropolitan City (BMC). A stratified random sampling approach was used to survey 186 HHs in November 2017. Semi structured questionnaires, key informant interviews (KIIs), and observational waste audits were used for data collection. Waste composition was analyzed following United Nations Environment Programme (UNEP) guidelines, revealing over 70% organic waste, with recyclables like plastics, paper, glass, and metals comprising the remainder. Household waste generation averaged 0.167 kg/person/day in BMC. Knowledge of waste segregation was high, attitudes were acceptable, but practices were moderate, one third segregating waste due to space constraints. Most of composting was organic waste, while inorganic waste was sold to vendors. Despite high KAP scores, systemic failures in collection infrastructure and policy enforcement undermine SWM efficacy. The study highlights SWM practices in these industrial wards, indicating that although residents possess good knowledge and attitudes regarding solid waste management, practical implementation is hindered by infrastructural and policy gaps.